Clinical cardiac MRI : with interactive CD-ROM - Bogaert, Jan; Dymarkowski, Steven; Taylor, Andrew M.; Al-Saadi, Nidal; Bosmans, Hilde; Hamaekers, Pascal; Hegde, Sanjeet R.; Muthurangu, Vivek; Ni, Yicheng; Razavi, Reza (Medical radiology., 2005)
This extensively illustrated volume has been specifically geared towards optimal use of MRI systems. The text provides essential theoretical background information: Imaging acquisition and potential pitfalls are also examined in detail. Most importantly, structured guidelines are provided on the interpretation of clinical data in the wide range of cardiac pathology that can be encountered.